Bisnis dalam Kebijakan Pergulaan Masa Pemerintahan Megawati Soekarno Putri - Fransiska D Dabutar (Dinamika Politik, 2013)
This research is a study about of business in the sugar policy of the reign of Megawati Soekarno Putri. The focus is examining about causes the business in sugar policy during the reign of Megawati Soekarno Putri. The findings of this study, among others, there are three important things to be the main cause of the business in the sugar policy. First, lack oversight of government, and second, sugar oligopolistic market; Third, businessman as a ruler. The method which is used is descriptive-qualitative method that is intended to describe an event in more detail. Keywords: Business, policy, import.